Optimizing early childhood executive function through Mbojo culture-based guidance and counseling services - Nasution, Nasution; Amin, Nur Syariful; Safitri, Andy Hasliyati Ike; Ahyansyah, Ahyansyah; Mawaddah, Sukma; Putri, Suci Nora Julina (Edelweiss Applied Science and Technology, 2025)
This study aims to optimize the executive function of early childhood through Mbojo culture-based guidance and counseling services in Bima City. The research method used a mixed-method with a sequential exploratory design. Qualitative data were obtained through interviews and observations, while quantitative data were collected using an executive function questionnaire covering aspects of attention regulation, self-control, planning, and emotional regulation. The instrument reliability test showed a Cronbach’s Alpha value of 0.856; thus, the instrument was declared reliable. The results showed that before the service was implemented, 41% of children still had executive functions that needed to be improved. After the implementation of Mbojo culture-based services, there was an increase in children’s abilities in regulating attention, controlling impulses, making simple plans, and managing emotions. Thus, Mbojo culture-based guidance and counseling services are proven effective in improving the executive function of early childhood. The outputs of this study include service implementation guidelines and recommendations for early childhood education institutions.